PERANCANGAN SISTEM INFORMASI IZIN CUTI KARYAWAN DENGAN MENGGUNAKAN FRAMEWORK Service Oriented Architecture (SOA) - fauzi yuni (Jurnal Riset Sistem Informasi dan Teknologi Informasi (JURSISTEKNI), 2021)
Niaga Nusa Abadi is a subsidiary of PT. Nojorono Tobacco International which has a parent in Kudus. The company, which has been operating for more than 80 years, is a distribution company of PT NTI and operates in supplying product needs to areas with 50 branches spread throughout Indonesia. The company has always been to build client trust by providing distribution services that are supported by a quality management system and reliable HR. The well-known products it distributes are Class Mild, Djinggo Minak, Aroma, Nikki Super, Niko International, Jazy Mild, Marathon and so on. Even though this company has been said to be large, but in the process of requesting leave employees still use a manual process that is able to hinder the process of requesting leave for employees. Implementation of "Employee Leave Permit Information System Design Using PHP Web-Based Service Oriented Architecture (SOA) Model" is one of the best solutions for planning corporate strategy and using supportive technology in the process of requesting employee leave. This information system is web-based to present information on employee leave request data processing using the Service Oriented Architecture (SOA) method and PHP and MySQL programming. The purpose of this system is to design, manage, implement employee leave requests at the company. The implementation of this information system is intended to make the employee leave application process more effective and efficient. This information system can be accessed using a browser device.